Composting oil palm wastes and sewage sludge for use in potting media of ornamental plants - Ramahsamy, Kala Devi; Abu Bakar, Rosenani; Ishak, Che Fauziah; Abdullah, Thohirah Lee (Malaysian Society of Soil Science, 2009)
The use of oil palm wastes, particularly the empty fruit bunch (EFB), frond and trunk as compost are now receiving greater attention by researchers. Currently, these organic waste materials have not been fully utilized on a large scale, either agriculturally or industrially, for manufacture of useful by-products. Another organic waste that needs to be appropriately disposed of in Malaysia is the sewage sludge. Co-composting these waste materials could potentially convert these wastes into value added product. The objective of this study was to determine the best formulation using oil palm wastes and sewage sludge in producing a composted material to be used as a potting media in horticulture. Composting different oil palm wastes with sewage sludge was carried out in the glasshouse using a polystyrene box. Shredded oil palm wastes (EFB, frond and trunk) were mixed with sewage sludge in 3 different ratios (1:0, 3:1 and 4:1 ratio) and adjusted to 60% moisture content. Based on the temperature, C/N, NH4+ -N and NO3- - N + NO2- -N patterns of the oil palm wastes added with sludge during composting, the EFB, frond and trunk added with sludge composts seemed to perform similarly.However, due to the small volume of compost, the temperature did not sustain > 45ºC because of dissipation of the heat. Oil palm trunk with sewage sludge at 4:1 ratio was found to be the most optimum compost as potting media for ornamental plants because of its texture suitable for potting media, not stringent or stiff, had high nutrient contents (2.05 % N, 0.640 % P, 1.39 % K, 0.705 % Ca, 0.229% Mg), pH 6.2 and low C/N ratio, 19.